Fibre length and loading impact on the properties of glass fibre reinforced polypropylene random composites. (1st May 2021) - Delli, Evangelia; Giliopoulos, Dimitrios; Bikiaris, Dimitrios N.; Chrissafis, Konstantinos
Abstract: Polypropylene composites have emerged as alternative materials for a wide range of applications requiring advanced mechanical and thermal properties including automotive and structural engineering. The choice of suitable polypropylene reinforcing agent enables higher flexibility, lightweight, mechanical strength and low production cost. This paper reports on the fabrication of short glass fibre reinforced random polypropylene by melt mixing. The mechanical and thermal properties of the random polypropylene/E-glass fibre composites exhibited a strong dependence on the fibre size varying from 1 mm to 0.3 mm and the various fibre contents, namely 10, 15, 20 and 30 wt%. Activation energy analysis suggested hindering of crystallization due to the presence of the fibres. However, a maximum yield strength of 29.4 MPa was measured for the 10 wt% fibre reinforced composites with an average fibre length of 1 mm. Furthermore, use of shorter fibres (average length of 0.3 mm) and a filler loading of 10 wt% resulted in a maximum elongation at break of 654%. Enhanced stiffness was also observed for fibre content up to 15%. These results suggest that the use of short glass fibres will allow the development of cost-effective and robust polypropylene composites adequate for a wide range of modern applications.